M. BURKHALTER, S. CHRISTIAN (eds.) - Konrad Wachsmann and the Grapevine Structure - Jerez Abajo, Enrique (ZARCH, 2018)
Marianne Burkhalter, Christian Sumi (eds.)Konrad Wachsmann and the Grapevine StructurePark Books, Zürich, 2018, 152 páginas. Idioma: inglés. 48€.ISBN: 978-3-03860-110-4